Exploring an Artificial Intelligence as Automated Feedback Program in EFL Writing - Fiki Setiawan; Annas Alkhowarizmi (ETERNAL (English Teaching Journal), 2025)
This study investigates the effectiveness of Artificial Intelligence (AI) tools, namely Grammarly, QuillBot, and Ginger Software, in providing automated feedback for English as a Foreign Language (EFL) writing among Indonesian undergraduate students. It examines the potential of these AI-powered applications in identifying and correcting grammatical, punctuation, and clarity issues and paraphrasing in student writing. This research applied a descriptive qualitative method involving document analysis and interviews. The study involved comparing these tools' corrective feedback and conducting interviews with EFL writing students to understand their perceptions of using these tools. The research findings indicate varying levels of error detection and correction suggestions across the tools, with some differences in their efficiency. While Grammarly, QuillBot, and Ginger Software show promise in enhancing EFL writing skills, the study highlights the importance of not solely relying on these tools. Key findings reveal that Grammarly excels in grammatical accuracy, QuillBot offers superior paraphrasing capabilities, and Ginger provides limited feedback in comparison.  It suggests that integrating AI feedback with traditional methods of teacher and peer reviews can lead to optimal writing outcomes. The paper also discusses students' perceptions of using these tools, noting a preference for Grammarly due to its simplicity and effectiveness. Students reported improved grammar and motivation but exhibited tendencies toward over-reliance, potentially limiting critical thinking and independent writing skills. However, some students exhibited over-reliance on these tools, potentially hindering their critical thinking and independent writing skills. The study emphasizes the importance of using AI-powered tools strategically, alongside human editing and critical thinking practices, to maximize EFL writing development.